Yield‐Stress and Creep Control Depot Formation and Persistence of Injectable Hydrogels Following Subcutaneous Administration. (2nd August 2022) - Jons, Carolyn K.; Grosskopf, Abigail K.; Baillet, Julie; Yan, Jerry; Klich, John H.; Saouaf, Olivia M.; Appel, Eric A.
Abstract: Hydrogels that can be injected into the body using standard needles or catheters enable a minimally invasive strategy to prolong local delivery of therapeutic cargo. In particular, physically cross‐linked hydrogels exhibit shear‐thinning and self‐healing behaviors enabling facile injectability and depot formation upon administration. While prior efforts to characterize these systems have focused on injectability and cargo release behaviors, prediction of cargo release in the body often assumes these materials form a depot rather than spreading out upon administration. Here, it is evaluated how hydrogel rheology correlates with depot formation and persistence following subcutaneous administration in mice with two physiochemically distinct, physically cross‐linked hydrogel systems. Calcium‐alginate and polymer‐nanoparticle hydrogel systems exhibit variable mechanical behaviors across several rheological properties (stiffness, viscoelasticity, yield stress, and creep). By relating measured rheological properties to depot formation and persistence time following subcutaneous administration, it is identified that yield stress is predictive of initial depot formation while creep is predictive of depot persistence for these two gel systems. Indeed, only materials with yield stresses >25 Pa form robust depots, and reduced creep correlates with longer depot persistence. These findings provide predictive insights into design considerations for hydrogel technologies capable of extended controlled release of therapeutic cargo. Abstract : The role of rheological properties in controlling hydrogel depot formation and persistence following subcutaneous administration is investigated. To allow for robust depot formation, the yield stress of material must exceed 25 Pa while depot persistence is predicted by creep behavior at tissue‐relevant stresses.